Intervensi dengan Pendekatan Reedukatif dan Power Strategy untuk Meningkatkan Perilaku Disiplin Tepat Waktu di Kalangan Mahasiswa Kelas Xyz - Ari Setyorini; Juni Anton (Humaniora, 2011)
The purpose of this study is to answer whether the intervention with reeducative approach and power strategy can improve punctuality behavior among students in the class XYZ. Methodology is carried out by using the method of intervention with reeducative approach and power strategy involving 55 students at the XYZ class who is in their third semester at a private university. Intervention is conducted by providing re-learning on the importance of timely discipline behaviors by using an agent of change in the course lecturers is considered as having power over these students. The average number of students prior to the intervention of delay is 16 people (29.9%) to 4 (7:27%) after intervention resulting in a decrease of 21.82%. Things that cause the success of this project is the advantages of interventions, among others, changing the mindset of the target behavior regarding lateness in class, with presence of education  during socialization, enabling awareness of the importance of internal discipline.